Performance of nitrogen and zinc on yield and physico- chemical composition of ber (Zizyphus mauritiana Lamk) fruits cv. Gola (Indian Journal of Arid Horticulture, 2025)
A field experiment was carried out to study the influence of different levels of nitrogen (250, 500 and 750g plant' year') and zinc sulphate (0.4, 0.6 and 0.8 per cent plant' year') on yield and physico-chemical composition of ber fruits. Applications of 500g nitrogen and 0.6% zinc sulphate plant exhibited highest fruit yield with maximum dry matter, pulp. pulp: seed ratio, TSS, ascorbic acid, reducing sugar, non reducing sugar, total sugars and minimum moisture and seed content.
Keywords: Ber; nitrogen; zinc; yield; physico-chemical quality parameters